Sampling Feed Components and Finished Feed - Herrman, Tim J. (My University, 1995)
This publication contains definitions of different types of samples and sampling procedures, methods and equipment used for sample collection, procedures for sample reduction and submission, procedures for receiving ingredients, and ways to use sample results to improve feed quality.
MF2036_1995_10
Keywords: MF2036; Crops; MF